How Does Privatization Work? Evidence from the Russian Shops - Barberis, Nicholas; Boycko, Maxim; Shleifer, Andrei; Tsukanova, Natalia (Journal of Political Economy, 1996)
We use a survey of 452 Russian shops, most of which were privatized between 1992 and 1993, to measure the importance of alternative channels through which privatization promotes restructuring. Restructuring is measured as major renovation, a change in suppliers, an increase in hours stores stay open, and layoffs. There is strong evidence that the presence of new owners and new managers raises the likelihood of restructuring. In contrast, there is no evidence that equity incentives of old managers promote restructuring. The evidence points to the critical role new human capital plays in economic transformation.